2022
DOI: 10.21037/tp-22-189
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of the curative effects and safety of endoscopic sinus surgery in children with chronic sinusitis with nasal polyps

Abstract: Background: At present, the surgical treatment of sinusitis with nasal polyps has made great progress, but its recurrence rate is still high. Therefore, this time, meta-analysis is used to study the therapeutic effect of endoscopic sinus surgery on children with chronic sinusitis with nasal polyps, analyze its effectiveness and safety, and provide theoretical basis for clinical treatment.Methods: Boolean logic searching was adopted to retrieve articles from various databases, including PubMed, Medline, and Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…(1) patients with complete medical records; (2) those without severe cardiovascular, respiratory, hepatic or renal diseases; (3) those with a preoperative American Society of Anesthesiologists (ASA) classi cation of I to III; (4) those who were 18-70 years old; (5) those without hormones and immunosuppressant used before surgery; (6) those whose operation time was 8-17 o'clock; (7) those without a history of pepticulcer disease; (8) those without a history of addiction to analgesic drugs; (9) those without a history of migraine disease; (10) those who could cooperate with physical examination and pain assessment. The exclusion criteria were as follows: (1) those with an operative time of < 60 min or > 180 min; (2) those with an operative bleeding volume of 20-200 ml; (3) those with intraoperative and postoperative allergic reactions; (4) those without cooperating with postoperative treatment and follow-up visits; (5) those with the developed severe infections after surgery; and (6) psychiatric patients.…”
Section: Study Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) patients with complete medical records; (2) those without severe cardiovascular, respiratory, hepatic or renal diseases; (3) those with a preoperative American Society of Anesthesiologists (ASA) classi cation of I to III; (4) those who were 18-70 years old; (5) those without hormones and immunosuppressant used before surgery; (6) those whose operation time was 8-17 o'clock; (7) those without a history of pepticulcer disease; (8) those without a history of addiction to analgesic drugs; (9) those without a history of migraine disease; (10) those who could cooperate with physical examination and pain assessment. The exclusion criteria were as follows: (1) those with an operative time of < 60 min or > 180 min; (2) those with an operative bleeding volume of 20-200 ml; (3) those with intraoperative and postoperative allergic reactions; (4) those without cooperating with postoperative treatment and follow-up visits; (5) those with the developed severe infections after surgery; and (6) psychiatric patients.…”
Section: Study Subjectsmentioning
confidence: 99%
“…Functional endoscopic sinus surgery (FESS) thoroughly removes diseased tissues and restores normal morphology and physiological function of nasal and sinus mucosa [4] . FESS, characterized by small trauma, a clear operative eld, and a broad surgical perspective, has been regarded as a preferred surgical technique for the treatment of CRS [5] . Although FESS causes tremendous pain in breathing, swallowing, and other postoperative maneuvers due to the anatomical structure of the surgical site and the peculiarities of physiological functions, such as postoperative head and face pain, especially in those with nasal packing and mainly manifests as nasal distension, and most in the whole head which seriously affects their sleep and diet [6] .…”
Section: Introductionmentioning
confidence: 99%
“…ERAS elements adopted by these studies ranged from 6 to 14. In terms of the research contents, ten studies [16,[21][22][23][24][25][26][27][28][29] had reported LOS, 13 studies [5,16,21,23,24,26,[28][29][30][31][32][33][34] had outcomes on the incidence of overall postoperative complication, nine studies [5,16,23,29,30,32,[35][36][37] reported PONV, eight studies [24,26,30,32,33,[35][36][37] on facial edema, seven studies [24,26,32,33,[35][36][37] on low back pain and urinary retention, five studies [21,23,…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Thirteen studies (a total of 1274 patients) [5,16,21,23,24,26,[28][29][30][31][32][33][34] reported overall postoperative complications. Specifically, 9 studies [5,16,23,29,30,32,[35][36][37] reported PONV (involving 926 CRS patients), 8 studies [24,26,30,32,33,[35][36][37] for facial edema (involving PLOS ONE…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation